Respiratory support in acute heart failure with preserved vs reduced ejection fraction. Issue 4 (11th December 2019) - Metkus, Thomas S.; Stephens, Robert Scott; Schulman, Steven; Hsu, Steven; Morrow, David A.; Eid, Shaker M.
Abstract: Background: There is little evidence addressing the use and differential impact of respiratory support in acute heart failure (AHF) patients with preserved (HFPEF) vs reduced (HFREF) ejection fraction. Therefore, our objective was to determine the usage and clinical outcomes of critical care respiratory support in AHF across the two populations. Hypothesis: Respiratory support would be associated with adverse outcome in both HFPEF and HFREF. Methods: We identified HFPEF, HFREF, invasive mechanical ventilation (IMV), and noninvasive ventilation (NIV) using International Classification of Disease‐Ninth Edition codes in the National Inpatient Sample between January 1, 2008 and December 31, 2014. We determined rates of IMV and NIV use. We identified predictors of need for IMV and NIV and the association between ventilation strategies and in‐hospital mortality in HFPEF vs HFREF. Results: 1.3 million AHF‐HFPEF and 1.7 million AHF‐HFREF hospitalizations were included; 5.98% of AHF HFPEF hospitalizations included NIV and 0.57% included IMV. Among HFREF hospitalizations, fewer (4.1%) included NIV and more (0.93%) included IMV. In HFPEF hospitalization, NIV use was associated with 2.24‐fold increased risk for death compared to no respiratory support in an adjusted model (HR 2.24 95% CI 2.05‐2.44) and IMV use was associated with 2.85‐fold increased risk for death (HR 2.85 95% CI 2.30‐3.53). This increased risk of in‐hospital mortality was similar among HFREF patients. Conclusions: Use of respiratory support is increasing among patients with both HFPEF and HFREF and associated with substantially increased mortality in both heart failure subtypes.